A Jack's Reef Horizon Settlement Cluster in the Central Scioto Valley. Issue 3 (September 2014) - Schwarz, Kevin R.
<x content-type="archive" xml:space="preserve">Abstract</x> In 1992, Mark Seeman proposed the existence of a Jack's Reef horizon in Ohio. Little professional research has been undertaken on domestic sites since then though. The Jack's Reef horizon subsumes the Intrusive Mound complex. Archaeological excavations for the Rockies Express-East gas pipeline project identified three sites in the central Scioto valley that provide evidence of Jack's Reef horizon occupations in floodplain and upland settings flanking the river valley. Radiocarbon dates confirm habitation associated with this late Late Woodland culture from cal A.D. 630–1000. Excavation and geophysical data reviewed in this article indicate intensive habitation of large base camps and small-scale residential bases, with secondary refuse disposal, distinctive ceramics, a curated bifacial lithic technology, and an expedient flake-tool technology.